2016
DOI: 10.1016/j.jcmgh.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Gastrointestinal and Colonic Motor Functions in Humans and Animals

Abstract: Synopsis Accurately measuring the complex motor behaviors of the gastrointestinal tract has tremendous value for the understanding, diagnosis and treatment of digestive diseases. This review synthesizes the literature regarding current tests that are used in both humans and animals. There remains further opportunity to enhance such tests, especially when such tests are able to provide value in both the preclinical and the clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 182 publications
(195 reference statements)
0
66
0
1
Order By: Relevance
“…Hence, a physiological movement in another part of the GI tract could be missed. This limitation is not present in high‐resolution manometry, which measures changes in pressure in each centimeter of the colon . Furthermore, the 3D‐Transit system does not directly measure amplitude of contraction pressure, which is often used to characterize and classify motor events.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a physiological movement in another part of the GI tract could be missed. This limitation is not present in high‐resolution manometry, which measures changes in pressure in each centimeter of the colon . Furthermore, the 3D‐Transit system does not directly measure amplitude of contraction pressure, which is often used to characterize and classify motor events.…”
Section: Discussionmentioning
confidence: 99%
“…Transfected cells were cultured with complete medium supplemented with 500 µg/mL of G418 for longer than 14 days. Polyclonal pools of stable cells were suspended in the stimulation buffer containing 0.1% BSA; then, cells were added (10 000 cells/well) in white 384-well plates containing test compounds and ACh (EC 20 ACh in the presence of PAM). The plates were incubated for 60 minutes at 37°C in the presence of 5% CO 2 .…”
Section: In Vitro Ip1 Assaymentioning
confidence: 99%
“…19 These migrating colonic contraction can be monitored by intracolonic pressure measurement (manometry) and direct measurement of smooth muscle contraction of the colon using implanted force transducers. 20 We selected the implantation of force transducers, because colonic contractions can then be monitored by telemetry in freely moving conscious dogs. In the basal condition, fasted overnight in this study, only small contraction occurred prior to a dose of T523.…”
Section: Colonic High Amplitude Propagated Contractions (Hapc) Arementioning
confidence: 99%
“…There are elegant basic science techniques to elucidate the molecular mechanisms of ion transport, but only recent studies provide insight into potential motor mechanisms involved in the development of diarrhea. 43 In most discussions about the basic mechanisms of diarrhea, motility is generally mentioned only briefly. Clinical studies have indicated that chronic watery diarrhea frequently has a major motility component, typically rapid transit through the gut, limiting the contact time between theoretically absorbable solutes and a normal epithelium.…”
Section: Secretory or Osmotic Diarrheamentioning
confidence: 99%